Jean-Paul Sartre: Mystical Atheist or Mystical Anthipathist - Kirkpatrick, Kate (European journal for philosophy of religion, 2013)
Jean-Paul sartre is rarely discussed in the philosophy of religion. In 2009, however, Jerome Gellman broke the silence, publishing an article in this journal in which he argued that the source of sartres atheism was neither philosophical nor existential, but mystical. Drawing from several of sartres works - including Being and Nothingness, Words, and a 1943 review entitled A New mystic - I argue that there are strong biographical and philosophical reasons to disagree with Gellmans conclusion that sartre was a mystical atheist. moreover, I question the likelihood of drawing any definitive conclusions regarding the sources of sartres ambiguous atheism.